Ticket Reservation System Design with Web-Based - Tata Sutabri; Alex Wijaya; Iin Seprina; Rahayu Amalia (Universitas Dharma Wacana, 2022)
At this time, the use of internet services as a means to obtain information is increasingly being used. Because of its broad reach and easy access to the internet, it is ideal when used as a means of promotion and means to publish information. Although the internet has a negative impact, the positive impact is given more and is very helpful for anyone who uses it. This ticket booking program aims to solve customers’ problems, such as during ticket ordering and looking for information about tickets or other things. Such as helping all customers whose access to ticketing counters is constrained by distance and time, facilitating customers and ticket sellers in the buying and selling process, promoting the company, and providing services to customers regarding online and on-time ticket bookings. The internet is a very potent medium for developing a dynamic and wide-scale information system; with the internet, information about anything can be obtained easily and quickly and can be accessed via smartphones or laptops that are widely used in the current era. Based on the various conveniences and functionalities possessed by the internet, a